2004
DOI: 10.1039/b406556e
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to internal rotation around the C–N bond in 3-(o-aryl)-5-methyl-rhodanines using NMR spectroscopy and computational studies. Electron density topological analysis of the transition states

Abstract: We have investigated the pairs of rotational isomers for six 3-(o-aryl)-5-methyl-rhodanines (Z = H, F, Cl, Br, OH, and CH3) using NMR spectroscopy and density functional theory (DFT) calculations. Electron density topological and NBO analysis has demonstrated the importance of non-covalent interactions, characterised by (3, -1) bond critical points (BCPs), between the oxygen and sulfur atoms on the thiazolidine ring with the aryl substitutents in stabilizing the transition states. The energetic activation barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Such repulsive interactions have also been analysed in biphenyl, [30] 2,6-difluoro-substituted biphenyls [31] and 3-(oaryl)-5-methylrhodanines. [32] The different torsion angles of the three phthalimide groups determined from the X-ray structure of 2 are situated in the broad flat minimum between 30 and 608 calculated for the model compound II (see Figure 3). The quantum chemical analysis of the electron density in the molecular geometry of the X-ray structure shows that there are four repulsive interactions between the electronic spheres of the phthalimide oxygen atoms and the nitrogen atoms of the heptazine unit (see Figure 4 and Table 3).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Such repulsive interactions have also been analysed in biphenyl, [30] 2,6-difluoro-substituted biphenyls [31] and 3-(oaryl)-5-methylrhodanines. [32] The different torsion angles of the three phthalimide groups determined from the X-ray structure of 2 are situated in the broad flat minimum between 30 and 608 calculated for the model compound II (see Figure 3). The quantum chemical analysis of the electron density in the molecular geometry of the X-ray structure shows that there are four repulsive interactions between the electronic spheres of the phthalimide oxygen atoms and the nitrogen atoms of the heptazine unit (see Figure 4 and Table 3).…”
Section: Resultsmentioning
confidence: 95%
“…The values of the electron density and the Laplacian of the electron density at the BCPs are of the same order of magnitude as in biphenyl [30] and 3-(o-aryl)-5methylrhodanines. [32] The BCPs under discussion have low electron densities of around 0.013 a.u. and small positive values for the Laplacian of the electron density.…”
Section: Resultsmentioning
confidence: 98%
“…Density functional theory (DFT) calculations of the rotational barrier of six 3-(o-aryl)-5-methylrhodanines were carried out by Yeliz Aydeniz et al They found good agreement with the available experimental results [8]. Geometry optimization for all the rotamers have been performed using density functional theory (DFT) at the B3LYP functional and 6-31G** basis set which has been proved to be an excellent method [9][10][11][12].…”
Section: Computational Detailsmentioning
confidence: 95%
“…Even at the ab initio level, the absolute value of the barrier to rotation of 2,2 0 -bipyridine was underestimated by 20-30%. Density functional theory (DFT) calculations of the rotational barrier of 3-(o-aryl)-5-methyl-rhodanines were carried out by (Aydeniz et al, 2004). They found good agreement with the available experimental result.…”
Section: Introductionmentioning
confidence: 69%